THU0326 ANALYSIS OF PHOSPHATIDYLINOSITOL 3-KINASE PATHWAY IN B CELL ACTIVATION OF SYSTEMIC SCLEROSIS PATIENTS. (June 2019) - Rapp, Judit; Telek, Vivien; Minier, Tunde; Czirják, László; Berki, Timea; Simon, Diana
Abstract : Background: B cell activation is an early event in the development of systemic sclerosis (SSc) as transcriptome profiling identified local B-cell activation in early diffuse cutaneous (dc) SSc skin biopsies. Autoantibody production is a widely investigated function of B cells in SSc but less attention has been devoted to the role of innate immune molecules and their receptors, like Toll-like receptors (TLRs). The classical B cell activation downstream of BcR and CD19 co-receptor engagement involves phosphatidylinositol-3 kinases (PI3K) signaling pathway that integrates the effects of multiple co-stimulatory receptors. Objectives: Our goal was to examine PI3K signaling by investigating the mRNA expression of 92 pathway related genes in B cells from early dcSSc patients. Akt is a central element of PI3K pathway, but it can also converge into innate receptor mediated pathways such as mTOR and MAPK. Thus for functional relevance we also analyzed the phosphorylation of Akt, S6 and NF-κB in B cells from early dcSSc patients. Methods: Twenty-one patients with early dcSSc were enrolled with disease duration of 2.0 (±1.2) years based on the date of the first non-Raynaud's symptom. 30% of patients received immunosuppressive therapy. Peripheral blood CD19+ B cells were purified from dcSSc patients and age- and sex-matched healthy controls (HC, n=15). mRNA expression of 92 B cell specific PI3K pathway related genes was measured using a Taqman qPCR array and was validated by individual qPCR. Isolated B cells were activated through BcR using anti-IgG/M antibody or anti-CD180 antibody, and their combination followed by flow cytometric analysis of phospho-Akt (S473), phospho-S6 (S235/S236) and phospho-NF-κB p65 (S529) positive cells. Results: Analyzing the expression of 92 PI3K pathway associated genes we found altered expression of molecules playing a role in alternate B cell activation and innate signaling. The expression of both IL-4 receptor and osteopontin (SPP1) was upregulated in B cells of untreated dcSSc patients, but became downregulated upon immunosuppressive therapy. Innate molecules like TLR4 and complement component 3 remained highly upregulated and the downregulation of CD180 was not inhibited by immunosuppressive treatment, thus may preserve the activated state of B cells in dcSSc. We aimed to model B cell activation via TLR4 and CD180 but LPS and endogenous ligands of TLR4 failed to activate isolated B cells. Since there are not known ligands of CD180, we investigated the effects of anti-CD180 itself and also its combination with BcR mediated stimulation of B cells. Analyzing the phosphorylation of the PI3K pathway-associated molecules revealed an impaired responsiveness of dcSSc B cells to anti-CD180 alone, and the combination of anti-CD180 and anti-Ig induced different phosphorylation patterns of Akt, S6 and NF-kB molecules in dcSSc and healthy controls (HC). Conclusion: Analysis of B cells from early dcSSc patients revealed that B cells possess molecular changes in PI3K pathway that involves innate immune components. Gaining new insight into innate B-cell activation in SSc could be helpful for finding new therapeutic targets. References: [1] Bhattacharyya S, et al. Adv wound care (2017) 6:356–369. [2] Chaplin JW, et al. J Immunol (2011) 187:4199–209. Acknowledgement: This work was supported by GINOP-232-15-2016-00050 and EFOP 361-16-2016-00004 grants. Disclosure of Interests: None declared